State Regulation of Employment in Kazakhstan: Labor Market and Ways of Development - G. S. Smagulova; A. A. Barzhaksyyeva (Экономика: стратегия и практика)
State regulation of population employment (hereinafter – SREP) is critical in ensuring national stability and prosperity. The present study aims to explore avenues for enhancing SREP in Kazakhstan and formulate actionable implementation proposals. The methodology employed encompasses scientific abstraction, comparative analysis through induction and deduction, communication analysis, statistical data analysis, and an integrated approach to generate comprehensive insights. The study reveals a 1-3% increase in the workforce and self-employed individuals over the past three years, which signifies moderate but consistent growth in labor participation. However, the COVID-19 pandemic led to a temporary 2% rise in unemployment in 2022, a setback followed by a reduction to 1% by the end of 2023, indicating a gradual improvement in labor market conditions. The study proposes innovative measures aimed at fostering job creation, especially in emerging sectors such as information technology and the “green” economy, emphasizing the need for strategic investment in these areas. Furthermore, recommendations are provided to support entrepreneurship and the development of small and medium-sized enterprises, which are pivotal for sustainable employment growth. The findings of this research indicate that the proposed measures have the potential to enhance employment levels and contribute to overall economic growth significantly. The contribution of this study lies in identifying effective strategies for further development and enhancement of SREP to increase employment opportunities and promote economic resilience in Kazakhstan. Future research will examine the impact of legislative changes on employment, the implications of automation and digitalization, and provide a comparative analysis of successful international employment regulation practices.